PENGEMBANGAN PROGRAM PEMBELAJARAN TERPADU PADA PEMBELAJARAN IPS DI SMP NEGERI 28 PALEMBANG - Deskoni Deskoni; Siti Fatimah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2014)
This research is a development research that aims to produce an integrated learning program in IPS lesson in SMP Negeri 28 Palembang for one semester and to know student learning activity in learning after having got treatment by using integrated learning program. This study uses the Brog and Gall product development model (Modified Sukmadinata, 2007). This development research was conducted in SMP Negeri 28 Palembang. Data collection techniques used are questionnaires, observations, documentation. Data analysis techniques using quantitative descriptive, that is by changing the quantitative data from the validation and trial results into qualitative data that refers to the validation and practicality criteria. After the product of integrated learning program developed then conducted one to one test, small group, and field test to test the validity, practicality, and potential effect of the product. In order to see students' learning activity, 2 experiments were conducted, which in the first meeting resulted 79,89% using conventional learning program, and obtained result of 82,60% at second meeting by using integrated learning program. From the results of this development research obtained a product of integrated learning program that can be used in IPS learning. As a result of the accompaniment of this development research, which received a positive response of 80.49% towards the use of integrated learning program on IPS learning.